Effects of argon and nitrogen plasma pulses on the skin and skin appendages in an in vivo animal model. Issue 1 (18th September 2019) - Kim, Heesu; Kim, Hyun‐Jo; Kim, Hee Kyung; Hong, Jeong Yeon; Cho, Sung Bin
Abstract: Background: For medical purposes, plasma can be generated from inert gaseous sources in a device by ultra‐high‐frequency generators and emitted to target tissue at a pulse duration in the milliseconds. Objective: To evaluate argon and nitrogen plasma pulse‐induced tissue reactions in the skin and skin appendages of an in vivo animal model. Methods: Argon and nitrogen plasma pulses were non‐invasively delivered to in vivo rat skin at various experimental settings. Specimens were histologically evaluated following hematoxylin and eosin and Masson's trichrome staining. Results: At low‐energy settings of 1.0, 1.5, and 2.0 J, nitrogen plasma treatments generated noticeable tissue coagulation at the depths of 31.5 ± 8.3, 94.9 ± 16.9, and 171.6 ± 19.7 µm, respectively, at Day 0. At high‐energy settings of 2.5 and 3.0 J, nitrogen plasma treatments generated marked tissue coagulation at the depths of 381.7 ± 33.6 µm and 456.3 ± 75.7 µm, respectively, at Day 0. Conclusions: Treatment with argon plasma induces microscopic changes in the epidermis, dermis, and sebaceous glands without generating excessive thermal injury, whereas that with nitrogen plasma elicits energy‐dependent thermal coagulation in the epidermis and dermis with remarkable neocollagenesis.